POLITICAL COMMUNICATION BASED ON IDENTITY POLITICS AND SOCIAL NETWORKING MEDIA IN THE PERIODE 2012-2017 DKI JAKARTA GOVERNOR ELECTION - Didin Sabarudin (Jurnal Komunikasi dan Bisnis, 2021)
The pattern of centralized government that turned into decentralized has brought a shift in the locus of power from the center to the regions, including changes in political authority at the local level. The spirit of democratization that occurred after the New Order regime had a follow-up impact in the form of decentralization with the enactment of Law No.22/2001 on Regional Autonomy which was later revised into Law No.32/2004 and Law 12/2008. The implementation of regional autonomy is an entry point for the rise of identity politics at the local political level. This condition occurs in the megapolitan city of Jakarta, whereas the capital of the country inhabited by residents from various identities. Identity-based mobilization was actualized by the pair of gubernatorial candidates who competed in the 2012 DKI Jakarta gubernatorial election, especially in the second round between the incumbent governor Fauzi Bowo who paired with Nachrowi Ramli (Foke – Nara) who came from the Betawi ethnicity against the pair Joko Widodo – Basuki Tjahaja. Purnama (Jokowi – Ahok) as a blend of Javanese ethnic identity comes from Solo and Chinese ethnicity from East Belitung, Sumatra. Key words: Identity Politic, Political Communication, Social Network Media, Governor Election.